Biogeochemistry of Uranium in Tropical Environments - Galhardi, Juliana A.; Bonotto, Daniel M. [UNESP]; Eismann, Carlos E. [UNESP]; Da Silva, Ygor Jacques A. B.; Gupta, D. K.; Walther, C. (Springer, 2020)
Uranium evaluation in areas affected by industrial, mining, and agricultural activities is important for the assessment of the human exposure to the natural radioactivity. Besides the occurrence of U isotopes in soils, rocks, and sediments being natural, anthropogenic activities contribute to increase this dose. Food and water ingestion is one of the main sources of U exposure to the population. Although the main U carrier is water, dust and atmospheric particulate matter also act as alternative routes to this radioelement dispersion. In soils, U mobility and its uptake by living organisms can be affected by physical and chemical properties of the mean. Until the present days, most of the studies examining the transference of U from soils, sediments, and natural waters to the biota took place in temperate and developed areas, where the use of the natural resources, climatic conditions, weathering processes, nutrient cycling, and metal uptake by living organisms differ significantly from those in tropical areas. In tropical areas, as soon as organic materials reach the soil surface, they are decomposed, with minimal accumulation of organic matter and a rapid recycling of nutrients and contaminants in vegetation. Mechanisms controlling the uptake of U by aquatic and terrestrial organisms in tropical regions deserve special attention considering that these areas are large producers of food worldwide. In this chapter, we consider the main environmental factors that control the U bioavailability in tropical aquatic and terrestrial ecosystems, providing useful information for risk assessment models.
Keywords: Uranium; Biomonitoring; Tropical areas; Natural waters; Tropical soils; Natural radionuclides